PENINGKATAN KETERAMPILAN MENULIS TEKS EKSPLANASI MENGGUNAKAN MODEL THINK TALK WRITE DI KELAS V SDN 40 SEI LAREH KOTA PADANG - Asahri, Putri Masayu; Suriani, Ari; Muhammadi; Sukma, Elfia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low explanation text writing skills among fifth-grade students at SDN 40 Sei Lareh, Padang, characterized by difficulties in organizing ideas, correct spelling, and limited vocabulary. This study aims to improve explanation text writing skills through the implementation of the Think Talk Write (TTW) learning model. This is a Classroom Action Research (CAR) using both qualitative and quantitative approaches, conducted in two cycles consisting of planning, implementation, observation, and reflection. The subjects were one teacher and 21 fifth-grade students. The results showed a significant improvement in every aspect. The quality of lesson planning (Teaching Module) increased from an average of 90 (Cycle I) to 95 (Cycle II). Teacher and student activities improved from the "fair" category (82.5) in Cycle I to the "excellent" category (95) in Cycle II. This improvement positively impacted student learning outcomes, where the average score for writing explanation texts increased from 74.64 (fair) in Cycle I to 83.25 (good) in Cycle II. It can be concluded that the Think Talk Write model is effective in improving explanation text writing skills for elementary school students. Keywords: Writing Skills, Explanation Text, Think Talk Write, Elementary School.